PROTOTYPE WEBSITE MAKANAN KHAS MELAYU BERBASIS TEPUNG DI KOTA PEKANBARU DAN PERSEPSI PEMAKAI TERHADAP DESAIN DAN KEMUDAHAN PENGGUNAANNYA (Studi Kasus Mahasiswa Jurusan Agribisnis Fakultas Pertanian Universitas Riau) - Roy Agustian; Roza Yulida; Dahliyusmanto ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Website is one of the media to get informations. One of the information is about traditional Malay foods. Pekanbaru have various traditional Malay foods, especially base on flour. Some of culinary website just show foods name. A culinary website needs shown specific information such foods history, food recipe, location, and others. the purpose of this research : 1) Desaigning the website of culinary traditional malay foods base of flour in Pekanbaru with Joomla 3.0. 2) Analyze the level of user satisfaction to culinary website traditional malay foods base on flour. 3) Analyze to level important and attributes performance culinary website traditional malay foods base on flour. Sampling uses non probability method that convience sampling. taking 90 samples uses slovin formula. Analyze of data using joomla 3.0, Customer Satisfaction Index (CSI), Important and Performance Analyze (IPA). Desaigning website include installation XAMPP for Joomla 3.0 aplication, offline installation joomla 3.0, and then desaigning website layout. The result of CSI show user satisfication has a value of 84.00 %. Base on the result of IPA, quadrant I has symbol. Quadrant II have Top Menu, accurate Information, Picture flash, Article, Content, hyperlink, clarity of information, speed of acess, and source. Quadran III have layout interface, attributes on website, user satisfication, and easy access. Quadrant IV have question column and viewers statistic. Key Words : Traditional Malay Foods Web, Joomla, User Perception, User                Satisfacation.